FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KUE SORABI HIJAU RENGASDENGKLOK - Sutrisyo, Herdwin Eka; Tecoalu, Melitina (Manajemen Bisnis Kompetensi, 2016)
ABSTRACTThis study aimed to analyze the factors that influence purchasing decisions Kue Sorabi Hijau Rengasdengklok. Purchasing decisions is important to be noticed by an UKM or a company to determine the factors that are considered by consumers or buyers. The data of this research was obtained from the primary data questionnaire. The sampling technique of this research is non probability sampling with the method of purposive sampling. The analysis technique used in this research are validity test, reliability test, classic assumptions test, multiple linear regression analysis, and hypothesis test including coefficient of determination (R2), the parameter partial test (t test) and Anova test (F test). The result of analysis using simultaneous test (F test) indicates that the variable price, brand image, product quality, location and word of mouth simultaneously / together have a positive effect of the purchase decision variables. The result of analysis using partial tests (t test) can be seen that price and word of mouth does not ffect the purchase decision, while brand image, product quality, and location have positive effect on purchasing decisions Kue Sorabi Hijau Rengasdengklok. The result of analysis using coefficient of determination (R2) the value Adjusted R Square of 0.685. This value means that 68.5% variable purchase decision can be explained from variable price, brand image, product quality, location and word of mouth, while 31.5% of purchase decisions is explained by others variable that excluded in this research.Keywords: Price, Brand Image, Product Quality, Location, Word of Mouth, Buying Decision